Water Requirement of Pomegranate (Punica granatum 1.) Orchards In Semi-arid Region of Maharashtra, India - Meshram, D T; Gorantiwar, S D; Mittal, H K (Annals of Arid Zone, 2016)
The study was carried out to estimate reference crop evapotranspiration, develop crop coefficient, area factor and estimate evapotranspiration of pomegranate for Nasik district of Maharashtra. The crop coefficient values were estimated on weekly basis from the concept of shaded area approach. Shaded areas were estimated at mid-day with the help of plywood board having 20 x 20 cm grid. Pomegranate evapotranspiration was determined on monthly basis using crop coefficient and reference crop evapotranspiration. The water to be applied through drip system at 90% efficiency to pomegranate plantation spaced at 3 x 4.5 m ranged from 1.4-4.3, 3.1-10.7, 2.6-30.4, 3.9-40.7 and 4.4-50.1 L dai1 tree- for 1st to 5th years. The values of reference crop evapotranspiration, crop coefficient, area factor, water requirement and water to be applied would be useful for the irrigation water management of pomegranate. Key words: Pomegranate (Punica granatum L.), reference crop evapotranspiration (ETr), crop evapotranspiration (ETc), crop coefficient (Kc), area factor, water requirement.